Fuel price increases and the timing of changes in household driving decisions - Cozad, Melanie; LaRiviere, Jacob (Journal of Environmental Economics and Management, 2013)
Using the oil price increase of 1979 as a natural experiment and several event study specifications, this paper finds evidence that the oil spike induced significant decreases in carbon emissions on both the intensive (miles driven) and extensive (auto fuel efficiency) margins. Further, it appears that substitution on the intensive margin occurred instantaneously whereas extensive margin substitution occurred with a significant lag. Given the timing of the changes, the results appear robust to the implementation of Corporate Average Fuel Economy (CAFE) standards over the same time period. These findings have important implications for estimating demand elasticities for durable goods with respect to energy prices and the price elasticity of fuels themselves.